Risk Management in Preclinical Trials as Part of an Overall Integrated Quality Management System - M. A. Zaytseva; M. B. Ivanov; A. B. Verveda; L. V. Lyanginen (Безопасность и риск фармакотерапии)
The implementation of a complex risk-oriented approach at all stages of drug development, including the preclinical research stage, is essential for ensuring drug safety, quality and effi cacy. The aim of the study was to justify the beneﬁts of introducing risk management into the integrated quality management system at the preclinical trial stage. The optimal approach to implementing risk management system at the preclinical stage is an overall process approach based on the international standard ISO 31000:2009 Risk management—Principles and guidelines. This approach as applied to a preclinical research centre includes a three-tier risk management system at the level of operational process subsystems, the level of the testing centre’s departments, and the level of an individual preclinical study. The common components of the subsystems may include concepts, organisational structure, information exchange system, documentation structure, etc. The process of risk management as applied to the subsystems includes risk identiﬁcation, analysis, assessment, and response to the risk. The response to the risk is an iterative process that includes selection of response options, response planning, and implementation of response activities from control procedures to corrective and preventive actions. The integration of the preclinical risk management system into the organisation’s overall management system, which includes the occupational health and safety management system and the quality management system, will enhance the capabilities of the individual systems to achieve a high quality level of research, preserve the staﬀ ’s professional health, make informed management decisions within the organisation, increase preparedness for external audits, and gain competitive advantages.